1970
DOI: 10.1042/bj1190511
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical aspects associated with an ethanol-induced fatty liver

Abstract: Isocaloric replacement of either the fat or carbohydrate content of the diet by ethanol (36% of the total caloric intake) produced fatty infiltration of the liver in rats. The increase in hepatic triglyceride content was associated with a decrease in both ATP and glycogen contents. Increased activity of mitochondrial Mg(2+)-stimulated adenosine triphosphatase paralleled the increase in the free P(i) content of the liver homogenate. During the regression of the fatty liver, glycogen contents returned to normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
8
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 21 publications
5
8
0
Order By: Relevance
“…This hypothesis is supported by the observation that glycogen stores are depressed after ethanol feeding [22], For example, in perfused livers which were freeze-clamped during 7EC metabo lism, glycogen levels were 12.1 pmol/g in liv ers from ethanol-fed rats, compared to 35.8 pmol/g in controls (data not shown). As a result of diminished glycogen stores, sub strate supply for the pentose phosphate cycle may become limiting.…”
Section: Thurman and Scholzsupporting
confidence: 69%
“…This hypothesis is supported by the observation that glycogen stores are depressed after ethanol feeding [22], For example, in perfused livers which were freeze-clamped during 7EC metabo lism, glycogen levels were 12.1 pmol/g in liv ers from ethanol-fed rats, compared to 35.8 pmol/g in controls (data not shown). As a result of diminished glycogen stores, sub strate supply for the pentose phosphate cycle may become limiting.…”
Section: Thurman and Scholzsupporting
confidence: 69%
“…Previous studies report that acute and chronic ethanol consumption reduce liver glycogen content (28,46,50,52); however, the mechanisms responsible for this adverse metabolic outcome are not known. Herein, we evaluated the impact chronic ethanol consumption has on diurnal oscillations in various glycogen metabolic processes using a mouse model.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, ethanol-induced decreases in hepatic glycolytic activity are paralleled by significant decreases in liver glycogen levels (47). Several studies have shown that both acute and chronic alcohol consumption reduce hepatic glycogen levels (28,46,47,50,52,53). However, the mechanisms underlying these ethanol-mediated effects on liver glycogen metabolism remain poorly understood.…”
mentioning
confidence: 99%
“…ATP dependent transport across membranes is in fluenced by ethanol. The chronic ingestion of ethanol by rats increases their hepatic activity of Mg++ stimulated adenosine triphosphatase with a fall in the hepatic concentration of ATP and a rise in Pi [Walker and G ordon, 1970], However, oxygen consumption under these conditions has not been determined. Inappropriate vasodilatation of superficial ves sels could increase the loss of heat that can only be replaced by an in creased catabolic rate.…”
Section: Discussionmentioning
confidence: 99%